1998
DOI: 10.1172/jci1666
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis induced by proteoglycan aggrecan G1 domain in BALB/c mice. Evidence for t cell involvement and the immunosuppressive influence of keratan sulfate on recognition of t and b cell epitopes.

Abstract: Our previous work showed that the proteoglycan aggrecan can induce erosive polyarthritis and spondylitis in BALB/c mice, and that the G1 domain of the proteoglycan aggrecan (G1) is the arthritogenic region. In this study, two T cell epitopes residing on G1 within residues 70-84 (peptide G5) and 150-169 (peptide G9) were identified using synthetic peptides and aggrecan-specific T cell lines. Two G1-specific T cell hybridomas exclusively responded to peptide G5. When the G5-specific T cell line was injected intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 32 publications
0
44
0
4
Order By: Relevance
“…The G1 domain of the proteoglycan aggrecan has been of special interest in the past, because an animal model resembling AS could be induced by immunization with this protein. However, CD8ϩ T cells do not seem to play a role in this model (25). A T cell response to aggrecan could also be demonstrated in peripheral blood in several rheumatic diseases, including rheumatoid arthritis, osteoarthritis, and AS (26,27).…”
mentioning
confidence: 78%
“…The G1 domain of the proteoglycan aggrecan has been of special interest in the past, because an animal model resembling AS could be induced by immunization with this protein. However, CD8ϩ T cells do not seem to play a role in this model (25). A T cell response to aggrecan could also be demonstrated in peripheral blood in several rheumatic diseases, including rheumatoid arthritis, osteoarthritis, and AS (26,27).…”
mentioning
confidence: 78%
“…A recent comprehensive proteomic surveillance has revealed that some Ags are recognized predominantly in OA rather than in RA (4). In animal models, immunization with cartilage proteins such as collagen type II, human cartilage glycoprotein-39 (44), cartilage link protein (45), and proteoglycans (46,47) induce destructive arthritis whereas cartilage intermediate layer protein (40) and YKL-39 (42) cause mild synovitis but no cartilage or bone destruction. Whether the immune reaction against these or other cartilage autoantigens play a role in triggering and/or perpetuating synovitis and cartilage damage in OA remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…1-4). Although RA is considered an autoimmune disease of unknown etiology, there has been no shortage of Ags proposed to be initiating or driving the autoimmune response, including viral proteins from CMV and EBV (5,6), autologous proteins expressed in diarthrodial joints such as link and proteoglycan (7)(8)(9), gp39 (10), and type II collagen (CII; Refs. [11][12][13][14].…”
Section: R Heumatoid Arthritis (Ra)mentioning
confidence: 99%